OPTIMALISASI PERAN GURU DALAM PENERAPAN BUDAYA POSITIF DI LINGKUNGAN SEKOLAH - Winda Oktaviana; Dewi Wijayanti; Maria Vionita Widiastuti; Apri Wahyudi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This mini-research aims to comprehensively analyze the optimization of the role of all school members and the involvement of parents/guardians in the implementation of positive culture (budaya positif) in an urban primary school setting, specifically at SDN 1 Kota Baru, Bandar Lampung. The study is motivated by the fundamental transformation in Indonesian national education through the Merdeka Curriculum, which positions character building as a main pillar, realized through the Profile of Pancasila Students. The research uses a qualitative approach with data collection techniques including interviews, observation, and documentation. The findings indicate that the Headmaster's policy and support are crucial, but the effectiveness of collaboration between the school and parents in the urban context is not yet optimal. The implementation of positive culture, including the use of restitution and positive discipline, is understood and practiced by teachers, but factors such as limited educational staff and complex external influences pose specific challenges. The study concludes that optimalization requires a responsive model that addresses the urban context, focusing on effective coordination among school components and enhanced, consistent collaboration with parents to ensure the uniformity of values between school and home environments.